A STUDY OF HEDONIC CONSUMPTION AND EXPERIENTIAL MARKETING IN THE PC/VIDEO GAMING INDUSTRY - Shanbhog, Krishna, M. (2007)
Traditional consumer research mostly focussed on the utilitarian benefits of goods and viewed the consumer as a rational decision maker who purchased and consumed products that offered practical utility, thereby ignoring important aspects of consumption phenomena that occurred in the form of experiential enjoyment. However from the early 80's there has been considerable attention given to the ÃÂexperiential view of consumer behaviour and consumption experiences. Ever since, there have been many studies that brought out the theoretical concepts of hedonic consumption, and also there were many empirical investigations in order to clarify these previously laid down concepts. Besides consumer behaviour, in the field of marketing, Experiential Marketing has started gaining a lot of pace since the mid 90's with quite a few theoretical concepts coming up. However, from the above theoretical concepts mentioned, there have been no significant empirical studies of these concepts in relevance of the PC/Video gaming industry, which currently is a multi billion dollars industry. An empirical investigation that studies these theoretical concepts in relevance of this industry will bring out significant implications for academics, marketers and game developers.